Comportamento infantil conhecido como hiperatividade: consequência do mundo contemporâneo ou TDAH? - Marilia Maria Gandra Gusmao (2009)
Child behavior known as hyperactive and usually diagnosed as ADHD (Attention deficit and hyperactivity disorder) is focused, with the purpose of verifying to what extent its origins can be related to excess of stimulation to which children are exposed in contemporary world. The hypothesis is that disorganized, disruptive and impulsive behaviors observed in many children diagnosed with ADHD would be a result of their psychological and social context. The study explores the ways this context contributes to the development of behavioral symptoms similar to ADHD ones. A qualitative approach is used in field research, based on the multiple case study method. Three children and the stimuli they receive in their everyday context were observed, especially their relationship to electronic devices like television, computers and video games. One child had been diagnosed as ADHD; another child presented in her behavior symptoms similar to ADHD, but without the disorder diagnosis; and another child presented behaviors considered normal. To carry out a deeper analysis of the collected data, the Self-Evaluating Scale for Children- SES-C has been used, considering that the children are able to assess their own behaviors and feelings. This scale, built by Klimkeit et al. (2006), has been translated to Portuguese by the Helena Antipoff Psychology and Education Research Laboratory team in order to contribute to a more effective ADHD diagnosis. The final results alert us to important factors that must be considered to prevent problematic behavior at school and at home: indiscriminate use of several modern electronic devices, fragile families that don´t impose limits to the children properly, the schools insufficient knowledge concerning behavioral problems that have appeared in the cultural and historical context within which we live, and the difficulty in finding the best solution to these problems, once the family not always provides enough support. The conclusion is that there is a close relationship between indiscriminate use of electronic devices and the appearance of behavioral problems, like hyperactivity and attention deficit. The study also has demonstrated that children´s troubles cannot be associated only to attention disorders, but more precisely to their difficulties to focus on school´s daily activities.